The impact of an eight-week aerobic and strength-training programme on agility and leg power of Malaysian netball players - Soh, Kim Geok; Husain, Ruby; Soh, Kim Lam (Faculty of Medicine, University of Malaya, 2007)
The purposes of the study were: (1) to determine the agility and leg power among Malaysian national junior netball players and (2) to determine the impact of eight-week aerobic and strength-training programme on these two variables. A total of 21 netball players from Bukit Jalil Sport School were selected as the subjects in this study. The SEMO Agility Run test was used to determine the agility level while leg power was measured using the Vertical Jump test. Pre-test and post-test results showed no significant differences in the agility and leg power level among the netball players. The mean values for the agility and leg power post-test were 12.59 (SD = 0.56) seconds and 50.24 (SD = 4.90) cm respectively. The pre-test and post-test results for different playing positions recorded the highest improvement in agility and leg power among attacker, followed by centre, and defender. Thus, the training conducted in this study was found to have improved agility and leg power marginally, especially among attacker and centre netball players.